Strengthening Uzbekistan’s Interregional Cooperation with Central Asian Countries Through Environmental Factors (Texas Journal of Multidisciplinary Studies, 2026)
This article analyzes the processes of strengthening the interregional cooperation of the Republic of Uzbekistan with the countries of Central Asia, particularly from the perspective of environmental factors. Based on the foreign policy priorities outlined in the Development Strategy of the New Uzbekistan for 2022–2026, the study highlights issues of regional integration and economic, cultural, and environmental cooperation. The ideas of peace, mutual trust, and solidarity promoted by Shavkat Mirziyoyev serve to further strengthen ecological and social cooperation among the states of the region